Biomimetics : nature based innovation - Bar-Cohen, Yoseph (Boca Raton : CRC Press, 2012)
'Based on the concept that nature offers numerous sources of inspiration for inventions related to mechanisms, materials, processes, and algorithms, this book covers the topic of biomimetics and the inspired innovation. The many recognized world-wide leaders that contribute to the text describe the efforts of turning science fiction ideas into engineering reality. This book is a follow-up to the authors 2005 publication and addresses many topics that were not covered in the original text. It reviews possibilities, the state of the art, and the challenges toward inspiring new experts to join the field. Extensive references at the end of each chapter are provided to enhance additional study'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Biomimetics; Biomimetics